(NsTIHOTWORENIQ(B: [1813-1824] /s (N~ASTX (B1s - (NpU[KIN(B, (NaLEKSANDR sERGEEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1974)
(Nw NASTOQ]IJ TOM SOBRANIQ SO^INENIJ a(B.(Ns(B. (NpU[KINA WO[LI LICEJSKIE STIHOTWORENIQ PO\TA I STIHOTWORENIQ (B1817-1824 (NGG(B.s
rus
Keywords: (NsTIHOTWORENIQs